Genetic variability and linkage disequilibrium within the HLA-DP region: analysis of 15 different populations. - Begovich, AB; Moonsamy, P; Mack, S; Barcellos, L; Steiner, L; Grams, S; Suraj-Baker, V; Hollenbach, J; Trachtenberg, E; Louie, L; Zimmerman, P; Hill, A; et al. (2001)
In order to understand the forces governing the evolution of the genetic diversity in the HLA-DP molecule, polymerase chain reaction (PCR)-based methods were used to characterize genetic variation at the DPA1 and DPB1 loci encoding this heterodimer on 2,807 chromosomes from 15 different populations including individuals of African, Asian, Amerindian, Indian and European origin. These ethnically diverse samples represent a variety of population substructures and include small, isolated populations as well as larger, presumably admixed populations. Ten DPA1 and 39 DPB1 alleles were identified and observed on 87 distinct DP haplotypes, 34 of which were found to be in significant positive linkage disequilibrium in at least one population. Some haplotypes were found in all ethnic groups while others were confined to a single ethnic group or population. Strong positive global linkage disequilibrium (Wn) between DPA1 and DPB1 was present in all 15 populations. The African populations displayed the lowest values of Wn whereas the Amerindian populations displayed near absolute disequilibrium. Analysis of the distribution of haplotypes using the normalized deviate of the Ewens-Watterson homozygosity statistic, F, suggests that DP haplotypes encoding the functional heterodimer are subject to much lower degrees of balancing selection than other loci within the HLA region. Finally, neighbor joining tree analyses demonstrate the power of haplotype diversity for inferring the relationships between the different populations.